A reestruturação produtiva no mundo do trabalho e o impacto nas políticas da educação superior no Brasil: o ensino superior a serviço do mercado de trabalho - Nascimento, Laisa Mirele Soares (2009)
This study was developed in the context of the Line of Inquiry of Politics and Management of the Education of the Program of Postgraduation in Education of the Federal University of Uberlândia UFU, which search to discuss questions made a list to the Education and I Work breaking it talks the relation between the professional formation in superior level and the labor market in the context of the productive restructuring in the world of the work. Since fountains of inquiry are used documents, laws and projects. It is considered that the whole state of affairs of the construction of the sense of the work and of the education at present articulates technological innovations with the new forms of organization and management of the production, in spite of the worker to be still essential for the realization of the work. One understands that the function in the society is being revised, since the society coexists with high taxes of unemployment. The current system it makes difficult enormous possible of men and women who sell his workforce, one lives in a quick society of consumption with the objective to speed up the reproductive cycle of the capital. The inquiry indicates that the official speech associates the idea of the schooling with the acquisition of a post of work, being so, the private higher education gains that it forces. These changes that do not manage to guarantee a better standard of living for the workers, a free time that could be used to guarantee the dignity of the man, aim only and exclusively the reproduction of the capital, provoking still more exploration of the workers.